The Effect of Social Security on Retirement in the Early 1970s - Hurd, Michael D.; Boskin, Michael J. (Quarterly Journal of Economics, 1984)
We analyze detailed longitudinal data on a cohort of males aged 58–67 in 1969–1973, a period of substantial increases in real Social Security benefits. We find the following: (1) the accelerating decline in labor force participation of elderly men in 1969–1973 can be explained by the large increase in real Social Security benefits; (2) there is evidence of a liquidity constraint effect for an important subgroup of the elderly; (3) the magnitude of this induced retirement effect is large enough that ignoring it can lead to serious underestimation of the fiscal implications of changes in benefit provisions. Our results are interpreted in the historical context of a particular cohort undergoing major, unanticipated transfers of wealth; the steady-state effects of Social Security on retirement may not be the same.